Sexual behavior and risk of sexually transmitted infections in medicine students of the national University of Cordoba - Leoni, Alberto F.; Martelloto, Gladys I.; Jakob, Ernesto; Cohen, Julio E.; Aranega, César I. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: the sexual transmission disease (STD) are common, affect young people, are increasing and can provoke severe trauma. The sexualbe havior have implications in the incidence. Objectives: to know the information, prevention attitude and evidence of risk factors among medicine students from the UNC. Methods: an individual, voluntary and anonymous study with a questioner of 32, in 1664 medicine students in the UNC. Results: in 1664 younger, 58% were women, the majority single and 99% heterosexual. The sexual debut was at younger age and the majority was with their partners. The number of sexual partners increase from 1º to 6º year. The students who manifested STD were 51. The preservative or condom was commonly used in younger, coincidentally with the reception of sexual education in this group. Conclusion: there’s a sexual debut at younger age, with an increase of partners in younger and prevention attitude less common within these group. Unless the majority has received sexualeducation, theses not reflected in a preventive attitude; the specific medicine information thus not influence the prevention behavior.